Modeling and Analysis of the Control System Drive in an Artificial Limb (International Journal of Current Engineering and Technology, 2015)
This study is an effort towards developing a linear mathematical model of the control system drive in an artificial limb using average value based approach. The design of the driving circuit is based on data’s obtained from video analysis of human locomotion. The user can enter the desired angle for actuating the driving circuit through the client module and the master controller helps in driving the DC series motors. The speed of the motors is controlled by Pulse Width Modulation (PWM) technique and is achieved with the help of 555 timer and potentiometer. The video analysis of the developed driving circuit was performed in the same manner as that of video locomotion analysis of subjects. The knee angle and hip angle dynamics involved in human locomotion is modeled by calculating the base average and the variational components. The developed mathematical model will be capable in designing the artificial limb having similar driving characteristics.
Keywords: Average value based approach; PWM; 555 timer; Locomotion